2012
DOI: 10.4236/wet.2012.34027
|View full text |Cite
|
Sign up to set email alerts
|

<i>A Brief Review</i>: Stage-Convertible Power Amplifier Using Differential Line Inductor

Abstract: In this review article, a stage-convertible RF power amplifier designed with a 0.18-m RF CMOS process is described. A method to implement a low-power matching network is an essential technology for the stage-convertible power amplifier. Various low-power matching networks with distributed active transformers as an output power combiner are compared in terms of the amounts of undesired coupling, the chip size, and the amount of power loss. The feasibility of a differential line inductor for the stage-convertib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Accordingly, the DAT provides successful solutions for the output matching networks of CMOS power amplifiers. Various studies related to CMOS power amplifiers using a DAT have been reported . Notably, with application of a DAT as the output matching network, the efficiency of the CMOS power amplifier has been dramatically improved.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the DAT provides successful solutions for the output matching networks of CMOS power amplifiers. Various studies related to CMOS power amplifiers using a DAT have been reported . Notably, with application of a DAT as the output matching network, the efficiency of the CMOS power amplifier has been dramatically improved.…”
Section: Introductionmentioning
confidence: 99%
“…The Helmholtz's theorem [1] states that any sufficiently smooth, decaying vector field in three dimensions can be decomposed into the sum of a curlfree (CF)/irrotational and a divergence-free (DF)/solenoidal vector components. The Helmholtz decomposition (HD) could capture field features, such as sources, sinks, and vortices [2]. Thus, it is a powerful visual tool in several applications involving aerodynamic design, detection of flow features, computer graphics, and so forth [3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the power amplifier is regarded as the component which determines the power efficiency of the overall mobile system, as the amplifier consumes most of the power from the battery. Efficiency improvement methods for power amplifiers remain one of the major challenges in today's pursuit of efficient mobile systems [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%